ANALISIS PENGARUH NILAI SUKUK, RATING SUKUK, DAN RISIKO SUKUK TERHADAP LAST YIELD SUKUK (Studi Kasus Perusahaan Konvensional non-bank yang Menerbitkan Sukuk di Indonesia Periode tahun 2008-2011) - Saraswati Almara, Dheni; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to examine the factors that affect last yield sukuk. This study uses three independent variables, namely sukuk value, sukuk rating, and risk of sukuk. with the dependent variable is the last yield of sukuk.The sampling technique used was purposive sampling criteria (1) The Company listed its sukuk on the Indonesia Stock Exchange, (2) the company has sufficient data to do research. The data sample obtained was 19 companies. The analytical method used is a multivariate regression. The assumption of classical test and hypothesis test using t-statistic, testing the coefficient of determination (R2), and the F-statistic to test the effect of model variables together with a significance level of 5%. This study also includes the classic assumption normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test.Based on the data normality test results, the study shows that the data are normally distributed. Based on the test results with the classical assumption of multicollinearity test, autocorrelation and heteroscedasticity test did not find any data that deviate from the classical assumption. It shows that the data used in this study are qualified to use a multivariate regression model. From the analysis in this study shows sukuk value has a negative correlation coefficient and no significant effect on last yield sukuk, sukuk rating has a positive correlation coefficient and no significant effect on the last yield sukuk, and risk of sukuk has a negative correlation coefficient and significant effect on the last yield sukuk.